HUBUNGAN KOMPONEN USAHA MENTAL (UM) DAN MENERIMA MENGOLAH INFORMASI (MMI) PADA PROSES PEMBELAJARAN BIOLOGI - Iffa Ichwani Putri (Program Studi Pendidikan Biologi Fakultas Ilmu Tarbiyah dan Keguruan Universitas Islam Negeri Raden Fatah Palembang, 2018)
Mental effort is the ability of students to face the existing learning environment. Mental effort will affect Extranous Cognitive Load (ECL). ECL can affect the ability to receive and process student information (MMI). MMI will affect the cognitive work memory of students in storing and processing data. This study aims to determine the relationship between UM and MMI of students in biology learning. This research is a descriptive study, with a sample of high school class XI students in Pekanbaru City who took excretory system material learning. The results showed that the UM scores of students were in the very low category which showed that the ECL of students was in the low category. The MMI value obtained by students is in a fairly good category. The correlation between UM-MMI shows an inverse relationship. This shows that the low UM can increase the MMI value and can support a decrease in the cognitive load of students in the learning process.